Urban drainage analysis using SWMM5: Case study of Sungai Kayu Ara, Damansara, Selangor - Mahyun, Ab Wahab; Ismail, Abustan, Prof. Madya Dr. (AUN/Seed-Net (ASEAN University Network/Southeast Asia Engineering Education Development Network, 2011)
1st Regional Conference on Geo-Disaster Mitigation and Waste Management in ASEAN organized by AUN/Seed-Net (ASEAN University Network/Southeast Asia Engineering Education Development Network, 3rd - 4th March 2009 at Kuala Lumpur, Malaysia.